Budaya “Gawai” Dalam Membentuk Nilai-Nilai Solidaritas Pada Masyarakat Suku Dayak Kalimantan Barat - Irmalini Syafrita; Mukhamad Murdiono (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The purpose of writing this article is to determine the Gawai culture in shaping the values of solidarity among the Dayak tribal communities in West Kalimantan. This article was prepared using the library research method, namely the method of collecting data by utilizing literature sources and materials. The result of the conclusion is that Gawai is a traditional Dayak ceremony which has become a tradition to this day. The Dayak gawai is one of the traditional ceremonies which is still actively carried out by the Dayak people. The Gawai Dayak traditional ceremony is one of the sources of local history in West Kalimantan. The implementation of the traditional Gawai ceremony aims to ask for safety and gratitude to God for the harvest which is usually done every one year. The traditional Gawai ceremony is held after the main harvest and ends with the traditional ritual of Rising Dango and reciting incantations and prayers or commonly known as Matik which aims to ask for blessings to God or Jubata. The implementation of the traditional gawai ceremony requires the involvement of all Dayak tribal communities to be able to work together in the preparation and implementation. Therefore, gadgets become the media needed to renew the spirit and sense of solidarity between Dayak tribal communities in West Kalimantan. The Gawai Traditional Ceremony is one of the very sacred religious rituals for the Dayak Tribe, therefore the Gawai Traditional ceremony only involves the Dayak Tribe. However, as the times progressed, the government tried to preserve the traditional Gawai ceremony, so that it became a routine tourism agenda in Pontianak City every year.